Pengaruh Likuiditas, Leverage, Arus Kas, dan Kepemilikan Institusional terhadap Financial Distress (Studi Empiris pada Perusahaan Sektor Propeties dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Renata Anissa Fikri; Wuri Septi Handayani; Amir Indrabudiman (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This research was conducted with the aim of determining the influence of liquidity, leverage, cash flow and institutional ownership on financial distress. This research was conducted on properties and real estate sector companies on the Indonesia Stock Exchange (BEI) with a research period of 2019-2023. The sample in this study used purposive sampling with a sample of 56 companies in the properties and real estate sector that met the sample criteria. The data analysis technique used in this research is multiple linear regression analysis using statistical testing tools, namely SPSS version 22.0. Based on the research results, it can be concluded that liquidity, cash flow and institutional ownership have a positive and significant effect on financial distress. Meanwhile, leverage has no effect on financial distress.